2014
DOI: 10.9790/0853-1374102109
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Adverse Drug Reactions-A Study of Clinical Patterns, Causality, Severity & Preventability

Abstract: Abstract:Aim-to study CADRs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
13
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 26 publications
5
13
3
Order By: Relevance
“…Female predominance (66.08%) was seen in this study. This is seen in accordance with studies conducted by Verma et al, Pudukadan et al and Chatterjee et al [12][13][14] This is however in contrast to studies where male predominance has been observed. 15,16 57.50% cases of ADRs were in the age group 21-40 years, also reported by Verma et al, Sharma et al, Leape et al had also observed that adults aged 20-49 years were at greatest risk of antibiotics-related drug eruptions, probably due to increased exposure to antibiotics.…”
Section: Discussioncontrasting
confidence: 40%
See 2 more Smart Citations
“…Female predominance (66.08%) was seen in this study. This is seen in accordance with studies conducted by Verma et al, Pudukadan et al and Chatterjee et al [12][13][14] This is however in contrast to studies where male predominance has been observed. 15,16 57.50% cases of ADRs were in the age group 21-40 years, also reported by Verma et al, Sharma et al, Leape et al had also observed that adults aged 20-49 years were at greatest risk of antibiotics-related drug eruptions, probably due to increased exposure to antibiotics.…”
Section: Discussioncontrasting
confidence: 40%
“…Verma et al and Sharma et al also reported similar findings. 12,16 Some other studies found fixed drug eruptions as the most common drug eruption followed by maculopapular rash and urticaria. 19 In this study steroids were implicated with maximum number of ADRs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 An adverse cutaneous drug reaction caused by a drug is any undesirable change in the structure or function of the skin, it's appendages or mucous membranes and it encompasses all adverse events related to drug eruption, regardless of etiology. 3 Although many of the skin reactions are not serious, some are lifethreatening such as Angio-edema, Stevens-Johnson Syndrome and Toxic Epidermal Necrolysis. 4 Studies have found the overall incidence of adverse drug reactions in skin in developed countries as 1-3 % and in the developing countries it is higher between 2-5%.…”
Section: Introductionmentioning
confidence: 99%
“…[1] An important risk factor for developing ADR is the previous occurrence of ADR. Re-exposure to offending drugs due to poor documentation can cause the patient to experience the same ADR again, thus emphasizing the importance of the accurate documentation of ADR at the time of the event and providing relevant information to the patient about the ADR will help prevent its further occurrence.…”
Section: Introductionmentioning
confidence: 99%